Formulation and in vitro Evaluation of Glimepiride Sustained Release Tablets: Comparison with Immediate Release Tablets - Karim, Samira; Bhuiyan, Mohiuddin Ahmed; Rana, Md Sohel (Bangladesh Pharmaceutical Journal, 2015)
This work aims at the design of a sustained release formulation of glimepiride which is currently available in the treatment of type 2 diabetes mellitus and to investigate the effect of polymers on the release profile of glimepiride. Glimepiride sustained release tablets were prepared by direct compression method using different ratios of various release retarding polymers such as carbopol, ethyl cellulose, methocel K4 MCR, methocel K15 MCR, methocel K100 MCR and xanthum gum. These formulations were also compared with glimepiride immediate release tablets. The prepared tablets were subjected to various physical parameter tests including weight variation, friability, hardness, thickness, diameter, etc. In vitro dissolution studies of the formulations were done at pH 6.8 in phosphate buffer using USP apparatus 2 (paddle method) at 50 rpm. The percent releases of all the formulations (30) were 73.11%- 98.76% after 8 hours. The release pattern followed zero order kinetics and the release of the drug was hindered by the polymers used in the study. On the other hand, 100% drug was released within 1 hour from the immediate release tablet of glimepiride. The study reveals that the polymers used have the capacity to retard the release of the drug from the sustained release tablets and the more is the amount of the polymer in the formulation the less is the release of drug showing more retardation of drug release. Bangladesh Pharmaceutical Journal 18(2): 157-162, 2015